COFFEE HUSK BASED ACTIVATED CARBON ELECTRODE SUPERCAPACITOR AS AN ALTERNATIVE TO RENEWABLE ENERGY STORAGE DEVICES IN INDONESIA - Andri Pangestu Purba; Mark Philip Purba; Mesakh L Tobing (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2021)
CO2 emissions from the use of fossil energy. However, the utilization of renewable energy sources has new challenges due to their intermittent nature and unequal distribution. Energy storage devices such as supercapacitors are needed to overcome these challenges. Therefore, it is very important to develop supercapacitor raw materials that are cheap, abundant, and environmentally friendly such as biomass waste. Coffee is a very promising commodity in Indonesia with total production reaching 742,000 tons per 2019. High coffee production implies the production of large-scale coffee husks which can be utilized to produce activated carbon. This paper aims to analyze the recent trends of characteristics of activated carbon from coffee husk as a material for the supercapacitor electrodes. Several types of activation agents are reviewed and compared. Scanning Electron Microscope technology and measurement with Brunauer-Emmett-Teller isotherm are used to identify the morphology and surface characteristics of activated carbon. Meanwhile, to analyze the chemical composition, energy dispersive X-ray spectroscopy and Fourier-transform infrared spectroscopy are used. Cyclic voltammetry and charge/discharge galvanostatic chronopotentiometry measurements are performed to evaluate the capacitance of the supercapacitor electrode cells. The obtained specific capacitance values range from 106 to 138 F g-1 with each specific surface area at a certain activation temperature. This paper is concerned about the concrete optimization of coffee waste as one of the largest sources of biomass energy in Indonesia. Keywords: coffee husk, activated carbon, supercapacitor, characterization, capacitance